Perbandingan Pemakaian Bahasa Indonesia dalam Konteks Formal dan Informal di Kalangan Mahasiswa Pendidikan Biologi UNIMED - Siregar, Rara Afifah; Lubis, Rizka; Aritonang, Nathasya Inneke; Sinaga, Gunis Enzlen; Pandiangan, Pinta; Tansliova, Lili (Comit: Communication, Information and Technology Journal, 2024)
This research aims to obtain data regarding the comparison of the use of Indonesian in formal and informal contexts among UNIMED Biology Education Students and to examine the use of formal and informal Indonesian in various communication situations among Biology Education students at UNIMED. This research method is quantitative. The population in this study were Biology Education students at Medan State University, with a sample size of 24 students. Research data was collected using a questionnaire technique consisting of 10 statement items. The research results show that based on survey results, the majority of respondents (70.8%) rarely use formal language in daily conversations on campus, indicating a tendency for casual communication between fellow students. However, a small majority (16%) often use formal language, while only (12.5%) always use formal language. Although the majority avoided using formal language regularly, none never used it, indicating an awareness of the importance of formal language in certain contexts, such as presentations, academic discussions, or interactions with lecturers.